Оцінка ефективності реконструкції житлових будинків - Гриценко, О. С.; Вахович, І. В.; Боліла, Н. В. (Ways to Improve Construction Efficiency, 2013)
In this article methodical approaches are considered for the estimation of efficiency of reconstruction of dwelling-houses with the aim of realization of economic analysis at the search of ways of decision of housing problem.